The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/s1701-2163(16)34886-1
|View full text |Cite
|
Sign up to set email alerts
|

RETIRED: Magnesium Sulphate for Fetal Neuroprotection

Abstract: This document reflects emerging clinical and scientific advances on the date issued, and is subject to change. The information should not be construed as dictating an exclusive course of treatment or procedure to be followed. Local institutions can dictate amendments to these opinions. They should be well documented if modified at the local level. None of these contents may be reproduced in any form without prior written permission of the SOGC. AbstractObjective: To provide guidelines for the use of antenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 44 publications
2
60
0
7
Order By: Relevance
“…25 In addition, randomized studies using magnesium sulphate for neuroprotection did not affect the incidence of the Apgar score <7 at 5 minutes (RR: 1.03, 95% CI: 0.9-1.18, three studies, 4387 newborn infants), neonatal hypotonia (RR: 1.02, 95% CI: 0.77-1.36, one study, 2444 newborn infants) or mechanical ventilation requirement (RR: 0.94, 95% CI: 0.89-1.00; three studies, 4387 newborn infants). 3 In turn, a subanalysis of the BEAM study (Beneficial Effects of Antenatal Magnesium Sulphate Trial) found no correlation between the magnesium level in umbilical cord blood and the requirement of ventilation, intubation or chest compressions. 3 In addition, there were no differences in terms of seizures, respiratory distress syndrome, bronchopulmonary dysplasia or necrotizing enterocolitis.…”
Section: Fetal Adverse Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 In addition, randomized studies using magnesium sulphate for neuroprotection did not affect the incidence of the Apgar score <7 at 5 minutes (RR: 1.03, 95% CI: 0.9-1.18, three studies, 4387 newborn infants), neonatal hypotonia (RR: 1.02, 95% CI: 0.77-1.36, one study, 2444 newborn infants) or mechanical ventilation requirement (RR: 0.94, 95% CI: 0.89-1.00; three studies, 4387 newborn infants). 3 In turn, a subanalysis of the BEAM study (Beneficial Effects of Antenatal Magnesium Sulphate Trial) found no correlation between the magnesium level in umbilical cord blood and the requirement of ventilation, intubation or chest compressions. 3 In addition, there were no differences in terms of seizures, respiratory distress syndrome, bronchopulmonary dysplasia or necrotizing enterocolitis.…”
Section: Fetal Adverse Eventsmentioning
confidence: 99%
“…3 In turn, a subanalysis of the BEAM study (Beneficial Effects of Antenatal Magnesium Sulphate Trial) found no correlation between the magnesium level in umbilical cord blood and the requirement of ventilation, intubation or chest compressions. 3 In addition, there were no differences in terms of seizures, respiratory distress syndrome, bronchopulmonary dysplasia or necrotizing enterocolitis. …”
Section: Fetal Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Что касается клинических исследо-ваний, то применение сульфата магния у женщин с повы-шенным риском преждевременных родов значительно снижает риск церебрального паралича у их детей, не уве-личивая при этом риск смерти [137,138]. В Австралии в национальные клинические рекомендации введен при-ем сульфата магния беременной с 31-й нед гестации в случае угрозы преждевременных родов с целью нейро-протекции ребенка [139]. В то же время не подтвержда-ется, что магний может предотвращать сами преждевре-менные роды, либо облегчать их течение [138,140].…”
Section: педиатрическая фармакологияunclassified
“…6 As such, EFM is recommended only for women with risk factors for adverse perinatal outcome, such as those requiring MgSO 4 for either prevention of eclampsia or fetal neuroprotection. 7 The use of MgSO 4 for fetal neuroprotection in the setting of imminent preterm birth for any indication at < 32 weeks is a relatively recent recommendation from the Society of Obstetricians and Gynaecologists of Canada, 7 and a Canadawide knowledge translation initiative has been undertaken within a quality assurance framework for tertiary obstetrical facilities. 8 This initiative has included educational site visits to these facilities, where questions were raised by physicians, midwives, and nurses about the effects of MgSO 4 on EFM, especially related to FHR variability.…”
Section: Introductionmentioning
confidence: 99%